The effect of project based learning model in seminar course to student’s creative thinking skills - Rindi Novitri Antika; Sulton Nawawi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
The purpose of this study was to determine the effect of Project Based Learning model of the student’s creative thinking skills. The methode used in this research was quasi-experimental. Subjects in this study were the seventh semester students of class C the experimental class and class A as the control. The results indicated that there was a significant increase of student’s creative thinking skills in experimental class compared to the control class which was indicated by N-gain test result (0.004 <0.05) in which the average of experimental calss was higher than the control class. The analysis per-indicator showed an increase of experimental class which the Fluence indicator was included in high category, the Flexibility and Originality indicators were fair, and the Elaboration indicator was low. These results were supported by the higher learning activity of student’s experimental class compared to those of control class. In addition, the student rerspons questionnaire showed a positive results to the application of the Project Based Learning model.